Spatial and temporal distribution of fishes in Cirata reservoir, West Java - Wahyuni, Sri; Sulistiono, Sulistiono; Affandi, Ridwan (Bumi Lestari; Vol 14 No 1 (2014))
This study aimedtoanalyze the relationshipbetweenthe condition ofthehabitatand thedistributionand abundance offishes spatially and temporallyin Cirata reservoir. Sampling offish conductedfrom February toJuly 2012in the Cirata reservoir. Fish sample sobtained from the catchesusinggillnetwithmesh size of1, 1.5, 2, 2.5, 3, and 3.5inches. Analysisconducted onphysical and chemical parameter water, substrat structure and abundance of fish, temporally and spatially. Fishobtainedduringthe studyamounted to626individuals,consist of 20speciesand10families. Cichlidaefamily foundin allof the studyzones.Based on physical and chemical caracter of water, Maleber zonewasthe best habitat. Dust was the dominan substratefractionin DAMzonewere (48.08%), Maniiszone(63.30%), Maleberzone(74.86%) andTegalDatar zone(58.93%). Substrate fractionintheJatinengangzone wasclay(56.78%), while thefraction ofthe substratein theRajaMandalazone was sand(46.56%).Fish speciesabundance ineachzone spatially were: DAM zoneis dominated by Oxyeleotrismarmorata(26.80%), Maniis zonewas dominated by Amphilopus citrinellus (43.05%), Maleber zone, Jatinengang zone and Raja Mandalazone were dominated by Oreochromisniloticus (28.79%), (44.11%),(39.75%), and Tegal Datar zonewas dominatedbyAequidens pulcher(74.69%). Abundanceof fishspeciesineachmonthtemporally: inFebruarywas dominatedbyHampalamacrolepidota (40.74%), Marchwas dominated by Oxyeleotrismarmorata(89.65%), Aprilwas dominatedbyChanos Chanos(62.79%), in Maywas dominatedbyHampalamacrolepidota(14.81%), Junewas dominatedbyAequidens pulcher(36.47%), and in Julywas dominatedbyMystusnigriceps(80.43%).
Keywords: Abundance, Cirata Reservoir, Spatial and temporal distribution